Analisis Pencemaran Air Pasca Penerapan Sanksi Terhadap Tindak Perusakan Konservasi Sumber Daya Air Di Sungai Silandak Kecamatan Ngaliyan Semarang - Nur Istiqomah; Zulfa Nurul Hidayah; Ahmad Fauzan Hidayatullah (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
Changes in river quality can reduce the optimal use of rivers for residents. The rapid development of industry in Indonesia, which is not balanced with a sense of responsibility towards the environment, can trigger water pollution. Liquid waste containing toxic materials that is flowed into rivers without being neutralized first can damage marine ecosystems and even kill aquatic biota. The study was conducted to find out the comparison between before and after sanctions were applied to water pollution in the Silandak River. The research procedure uses field observations of water conditions such as color, turbidity, aroma, amount of water, and current by taking pictures using a smartphone camera and recording observations using ATK. In addition, interviews were conducted with local residents. The results showed that there was a comparison between before and after handling. The color indicator was light brown, the level of turbidity was low, there was no foul smell, and the river flow was heavier than before. The existence of handling or efforts to overcome environmental problems so that the community is not disturbed again due to waste disposal without being processed first.